Effect of surface treatment of prefabricated teeth on shear bond strength of orthodontic brackets - Cumerlato,Marina (2017)
ABSTRACT Objective: The aim of this in vitro study was to evaluate and compare the effects of grinding, drilling, sandblasting, and ageing prefabricated teeth (PfT) on the shear bond strength (SBS) of orthodontic brackets, as well as the effects of surface treatments on the adhesive remnant index (ARI). Methods: One-hundred-ninety-two PfT were divided into four groups (n = 48): Group 1, no surface treatment was done; Group 2, grinding was performed with a cylindrical diamond bur; Group 3, two drillings were done with a spherical diamond bur; Group 4, sandblasting was performed with 50-µm aluminum oxide. Before the experiment, half of the samples stayed immersed in distilled water at 37oC for 90 days. Brackets were bonded with Transbond XT and shear strength tests were carried out using a universal testing machine. SBS were compared by surface treatment and by ageing with two-way ANOVA, followed by Tukey’s test. ARI scores were compared between surface treatments with Kruskal-Wallis test followed by Dunn’s test. Results: Surface treatments on PfT enhanced SBS of brackets (p< 0.01), result not observed with ageing (p= 0.45). Groups II, III, and IV showed higher SBS and greater ARI than the Group 1 (p< 0.05). SBS was greater in the groups 3 and 4 (drilling, sandblasting) than in the Group 2 (grinding) (p< 0.05). SBS and ARI showed a positive correlation (Spearman’s R2= 0.57; p< 0.05). Conclusion: Surface treatment on PfT enhanced SBS of brackets, however ageing did not show any relevance. Sandblasting and drilling showed greater SBS than grinding. There was a positive correlation between SBS and ARI.